THE GENERAL AEROBIC RESISTANCE AND BODY-MASS INDEX IN THE AGED THAT PRACTICES AQUATIC ACTIVITIES. (Fiep Bulletin - online, 2014)
The general aerobic resistance (RAG) is an important capacity for the performance in the functional activities of the aged ones, and can be influenced for the corporal composition. Objective: Evaluate the RAG and the body mass index (IMC) in aged that practice hydro gymnastics and swimming. Methodology: 52 aged ones with average age of 68,62 (+ 4,8) years had been evaluated, participants of the swimming programs (n=12) and hydro gymnastics (n=40) in the Group of Studies of the Third Age (GETI). It had been carried through measured anthropometrics referring to the calculation of the BMI; the RAG was evaluated through the test of walking half mile, that composes the battery of aged tests for of the AAHPERD in a track of atletismo of 200 meters, being the results written down in minutes and seconds. Results: In RAG scores, 26.9% had "very weak" scores,  28.8% "weak", 17.3% "regulate", 5.8% "good" and 21.2% "very good". In order to the BMI, 13.5% had been classified as "normal", 53.8% with "overweight" and 32.7% with "obesity".It was found significant difference in the test of Kruskal-Wallis (19,18), between the values of BMI and the levels of RAG, with a significance level of 0,05. Conclusion: The results had shown high indices of BMI associates with low scores of RAG in active aged women. These findings take us to consider that only the physical activity was not enough for reduction in the indices of BMI, and that the increment of alimentary programs could bring more efficient results for this variable; thus the effect of the aquatic activities in the aerobic resistance would be optimized.
Keywords: General aerobic resistance; Body mass index; Aquatic activities